Seven Decades of Econometrics and Beyond A Tribute to the Life and Work of Marc Nerlove - Baltagi, Badi H.; Mátyás, László (Advanced Studies in Theoretical and Applied Econometrics, 2025)
XXIII, 479 p. 46 illus., 32 illus. in color.